Integral Inequalities on Time Scales via the Theory of Isotonic Linear Functionals - Matloob Anwar; Rabia Bibi; Martin Bohner; Josip Pečarić (Abstract and Applied Analysis)
We apply the theory of isotonic linear functionals to derive a series of known inequalities, extensions of known inequalities, and new inequalities in the theory of dynamic equations on time scales.